Analisis Multikelompok Loyalitas dan Kepuasan Pelanggan GoFood: Peran Gender dan Lama Penggunaan - Adhika Putra Wicaksono; Vanessa Marshanda Elim; Juliani Dyah Trisnawati (Journal of Business & Banking, 2025)
This study examines the determinants of customer loyalty in the online food delivery service GoFood by analyzing the role of customer sat-isfaction and testing the moderating effects of gender and length of service usage. The research addresses the increasing competition in digital food delivery platforms and the need to understand behav-ioral differences among users. The purpose of this study is to ana-lyze the influence of service quality and perceived value on custom-er satisfaction and loyalty, and to determine whether gender and duration of use strengthen these relationships. This research em-ploys a quantitative approach, using a survey with structured questionnaires administered to GoFood users in Surabaya. The da-ta were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) and multigroup analysis. The findings indi-cate that service quality and perceived value significantly influence customer satisfaction, which in turn has a positive and significant effect on customer loyalty. Furthermore, the multigroup analysis reveals differences in the strength of relationships based on gender and length of usage. The results imply that digital platform pro-viders should adopt differentiated marketing strategies to enhance long-term customer loyalty.